Meningkatkan Literasi dan Numerasi melalui Komik Interaktif Matematika Dasar dengan Pendekatan CRT di SDN Barembeng 1 - Abdullah, Hasrianah; syamsuadi, ahmad; Ningsih, Fitria Wahyu; Rusdi, Nur Risma; Ulpa, Nur Aulia; Khaerunnisa; Mangindara, Mutmainnah; Magfirah; Ainun, Nurfadilah (Jurnal Pengabdian Kepada Masyarakat Patikala, 2024)
Interest and motivation for mathematics lessons is still very low, students consider mathematics to be a difficult and abstract subject, so they have difficulty understanding it. The approach to teaching mathematics which is often focused on memorizing formulas or abstract concepts makes students feel burdened, even tend to be afraid of this lesson. As a solution to this problem, the use of basic mathematics comic media with the Culturally Responsive Teaching (CRT) approach or Responsive Learning to Culture is expected to improve students' literacy, numeracy, and understanding of mathematics lessons. The method of implementing KOMIKDAS activities is divided into three stages, namely planning, implementation, and reporting. After the introduction of KOMIKDAS learning media took place, student learning outcomes increased by up to 90% from the results of the pretest and post-test tests given. In addition to increasing grades, children's attitudes towards mathematics learning also changed. This can be seen from the response to learning activities with a pleasant learning atmosphere due to the use of interesting learning media, namely through comics with the language and culture of everyday students. For further activities, it is suggested that comic media be developed with a wider variety of materials and difficulty levels to suit the abilities of all students. Teachers also need to be more actively involved through short training so that this media can be used sustainably in daily learning. In addition, stories in comics can raise more local values ​​and culture to strengthen students' sense of pride in their Keywords: Literacy, Numeracy, Mathematics Comics and CRT Approach.